Idiopathic thrombocytopenic purpura and MMR vaccine. Issue 3 (1st March 2001) - Miller, E; Waight, P; Farrington, C P; Andrews, N; Stowe, J; Taylor, B
Abstract : A CAUSAL ASSOCIATION BETWEEN MEASLES: mumps–rubella (MMR) vaccine and idiopathic thrombocytopenic purpura (ITP) was confirmed using immunisation/hospital admission record linkage. The absolute risk within six weeks of immunisation was 1 in 22 300 doses, with two of every three cases occurring in the six week post-immunisation period being caused by MMR. Children with ITP before MMR had no vaccine associated recurrences.